Challenges of Caring today from the Philosophy of Florence Nightingale (Salud, Arte y Cuidado, 2024)
There is a risk of dehumanization in the care of the person due to the great administrative and technological restructuring of most health care systems, however, despite the fact that Nursing should not be alien to the progress of computer advances, for Above any advance, there is respect for the life of the human being, technology is not a paradigm of care opposed to human contact, but, mainly, an agent and an intermediary of that contact, it is a means not an end in itself , Florencia Nightingale offers us the principles of care that we must return to in these times of change, so as not to lose our essence.